Penerapan Peraturan Menteri Agraria/Kepala Badan Pertanahan Nomor 21 Tahun 2020 Dalam Penyelesaian Sengketa Tanah Melalui Mediasi : (Study Di BPN Lombok Tengah) - Lalu Muhammad Wira Arizki; Arief Rahman; M. Yazid Fathoni (Private Law, 2023)
This study aims to determine the application of the Regulation of the Minister of Agrarian Affairs/Head of the National Land Agency of the Republic of Indonesia Number 21 of 2020. Furthermore, this study analyzes the Supporting and Obstacle Factors in the Land Dispute Resolution Process through the Mediation Process. The research method used is the empirical legal research method. The results of this study reveal that the settlement of land disputes at the Central Lombok National Land Agency through mediation has been running well and optimally. There are many land disputes resolved through non-litigation channels, namely mediation. The supporting factor of the mediation is the regulations that facilitate and clarifies in resolving land disputes. The inhibiting factors in land dispute resolutions through mediation at the Central Lombok District Land Office include, first, the parties did not have good intentions, they instead take advantage of the mediation process to stall for time, pretending to forget or dishonesty in resolving disputes. Second, the parties in land disputes insisted to defend their respective rights.